Subharmonic solutions with prescribed minimal period for a class of second order impulsive systems - Liang Bai; Xiaoyun Wang (Electronic Journal of Qualitative Theory of Differential Equations, 2017)
Based on variational methods and critical point theory, the existence of subharmonic solutions with prescribed minimal period for a class of second-order impulsive systems is derived by estimating the energy of the solution. And an example is presented to illustrate the result.